PENGARUH LINGKUNGAN BELAJAR DI SEKOLAH TERHADAP HASIL BELAJAR SISWA SMP NEGERI 12 PONTIANAK - Uswatun Hasanah; Nuraini Asriati; Sri Buwono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis study is to determine the effect of the school learning environment on student learning outcomes in social studies subjects in class VII in Pontianak 12 Public Middle School. The method used is descriptive in the form of quantitative research. The research sample consisted of class VII, the data in the form of a learning environment questionnaire at school. The results showed that the factors included in the school learning environment were teacher factors, physical environment, non physical or social environment, the most dominant factor being the physical environment with a percentage of 67%. The second problem formulation of 64 student learning outcomes is not complete in social studies because teacher teaching is not interesting, teacher and student relations are not good, student and friend relations are not good, this is supported by data analysis on teacher factor Summary Model, social environment or non physical. Based on the data analysis, the regression equation obtained is determination coefficient of 0.103, with a percentage of 10.3%, Adjusted R Square of 0.064 contributions of the influence of the school learning environment on student learning outcomes by 64%, while 36% is influenced by other factors not possessed by social studies. Keyword:  Social Studies Subjects, School Learning Environment, Student Learning Outcomes